Koli women displaying team effort - Mumbai Archive Project Team (Jio Institute, 2024)
The setup may look chaotic, but each team member has a clearly assigned role. Some run the kitchen, cleaning, marinating, cutting vegetables, and frying, while others look after the front desk, which includes taking orders, making payments, serving tables, and dispatching home deliveries.